Market Access under the World Trade Organization: Identifying Sensitive Agricultural Products in the EU - Huan-Niemi, Ellen (MTT, 2007)
The WTO negotiations dragged on for over seven years because of the divergent interests of the WTO members. Even among the developed countries, the United States (US) has different interests compared to the European Union (EU). The US is aggressively demanding for significant reduction in tariffs. Compared to the US, the EU is unable to lower its tariffs drastically because further tariff reductions will erode border protection for some of its important agricultural products. In this study, EU agricultural products are examined by tariff lines at eight digit level to reveal the sensitive agricultural products in the EU. These products are butter, skim milk powder, beef meat, poultry meat, pig meat, white sugar, wheat, barley, and maize. A spreadsheet model is used as an analysis tool to complement the various modelling approaches in identifying the sensitive agricultural products of the EU. The spreadsheet projection model is a simple forecasting model that uses a set of projection values from other models to predict possible outcomes. The sensitivity of EU agricultural products is analysed with various exchange rates (USD 0.90 per Euro to USD 1.50 per Euro), different tariff reduction formulas (according to the EU proposal, WTO draft proposal, and US proposal), and the scale limits in the Draft formula and US formula. Out of the many proposals submitted to the WTO for the tariff reduction formula, the US proposal is the most extreme and the EU proposal is the most lenient with the G-20 proposal and the WTO draft proposal being in the middle. It is natural that the EU proposal will generate a lower number of sensitive products compared to the WTO draft proposal, and the US proposal will generate the highest number of sensitive products. The results demonstrate that cereals such as wheat, barley, and maize are the most resilient to the erosion of border protection due to further reduction in tariffs in the projected Doha Round. In contrast, poultry meat has the weakest border protection in the projected Doha Round. The examined EU agricultural products are very sensitive to the fluctuations of exchange rate. In the projected Doha Round, there are no sensitive agricultural products in the EU if the Euro is very weak - USD 0.90 per Euro. On the contrary, a very strong Euro (USD 1.50 per Euro) will create the highest amount of sensitive products in the projected Doha Round. WTO members are entitled to select and designate an appropriate number of sensitive products. Proposals have extended from as little as one percent to as much as fifteen percent of tariff lines. The EU has proposed eight percent of the tariff lines to be designated as sensitive products in contrast to the proposal for only one percent by the US and G-20 group. The WTO draft proposal estimated that the number of sensitive products may be between four to eight percent of all agricultural tariff lines. Thus, the EU may be eligible to designate between 88 to 176 tariff lines as sensitive products. This study has analysed only nine tariff lines out of the 2200 tariff lines for EU agricultural products. The examined EU agricultural products may represent other tariff lines in the same product category, but potential sensitive products at eight digit level have to be analysed individually in order to choose the correct and exact number of sensitive products for the EU.
Keywords: Ma; WTO; EU; WTO; EU; Doha round; tariffs; sensitive agricultural products; border protection; exchange rates